Silicon-carbon negative electrode material, preparation method thereof and battery
Through step-by-step optimization of silicon deposition and carbon coating, a silicon-carbon composite material with specific structures and properties is formed, which solves the problem of capacity attenuation and poor circulation performance caused by volume expansion of silicon-carbon materials in lithium-ion batteries, and achieves the effect of improving battery performance and circulation stability.
Patent Information
- Application Number
- CN202510010558.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-03
AI Technical Summary
Silicon-carbon materials tend to expand in volume during the process of embedding/removing lithium ions, resulting in poor capacity attenuation and circulation performance.
The silicon deposition and carbon coating are precisely controlled through step-by-step operations, and the deposition morphology of silicon and the coating effect of carbon are optimized to form a composite material with specific structure and properties.
It improves the conductivity and structural stability of the material, reduces the direct contact between silicon and the electrolyte, and reduces the occurrence of side reactions, thereby improving the performance and cycle stability of the battery.
Smart Images

Figure BDA0005228239570000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode material preparation, and in particular relates to a silicon-carbon negative electrode material, a preparation method thereof and a battery. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] After half a century of development, the performance of lithium-ion batteries has been continuously improved in terms of energy density, power density and life. Anode materials such as carbon, transition metal oxides, SnOx, tin alloys and oxides, and silicon have been widely studied as important components of lithium-ion batteries. Among these anode materials, silicon materials have long been a hot topic in the field of research on new high-capacity anode materials due to their superior properties such as high theoretical specific capacity, large number of lithium ion storage, abundant resources and low price. However, silicon materials are prone to volume expansion during the process of embedding / de-embedding lithium ions, which leads to capacity decay and poor cycle performance.
[0004] Surface modification is usually an effective strategy to alleviate the internal stress caused by silicon volume expansion. Therefore, how to effectively modify the surface of silicon-carbon materials is the key to solving the above problems. Summary of the invention
[0005] In order to effectively solve the problem that silicon-carbon materials are prone to volume expansion during the process of embedding / de-embedding lithium ions, the present invention provides a silicon-carbon negative electrode material, a preparation method thereof, and a battery.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] In a first aspect, the present invention provides a silicon-carbon negative electrode material, comprising a porous carbon substrate, a nano-silicon layer deposited on the surface of the porous carbon substrate, a carbon coating layer deposited on the surface of the nano-silicon layer, and a passivation layer attached to the surface of the carbon coating layer.
[0008] During the experiment, the inventor tried to deposit a mixed gas silicon source and a carbon source together, but found the following problems: On the one hand, the deposition form of silicon has a great influence on the battery capacity and battery life. Since the silicon source and the carbon source are deposited together, the deposition form of nano-silicon is difficult to accurately adjust and optimize, and thus it is difficult to ensure the battery capacity and battery life. On the other hand, the carbon source and the silicon source are deposited together, and in the deposited layer formed, the carbon layer is discontinuous and non-dense, resulting in weak conductivity and structural stability of the negative electrode material. In addition, after the carbon source and the silicon source are mixed and deposited, attempts have been made to passivate the surface of the mixed deposited layer, but it is still difficult to ensure that the passivation layer is well isolated from the internal silicon-carbon mixed deposited layer, and it is easy for the silicon-carbon composite deposited layer to contact with the electrolyte, thereby corroding the silicon-carbon composite deposited layer, affecting the performance and life of the battery.
[0009] The preparation method of the present invention performs step-by-step operations on silicon deposition and carbon coating, which can achieve precise control of the silicon deposition and carbon coating processes. By adjusting deposition parameters (such as temperature, pressure, time, etc.), the deposition morphology of silicon and the coating effect of carbon can be optimized, thereby obtaining a composite material with a specific structure and performance. And the step-by-step process helps to form a more uniform and dense carbon coating layer. This can not only improve the conductivity and structural stability of the material, but also reduce the direct contact between silicon and the electrolyte, reduce the occurrence of side reactions, and thus improve the performance and cycle stability of the battery.
[0010] In a second aspect, the present invention provides a method for preparing the silicon-carbon negative electrode material, comprising the following steps: placing the porous carbon material in an inert atmosphere, heating it for pretreatment, and removing impurities and moisture on the surface of the material;
[0011] Vapor-depositing a nano-silicon layer on the surface of the pretreated porous carbon material;
[0012] Then, a carbon coating layer is deposited on the surface of the nano-silicon layer;
[0013] The surface of the carbon coating layer is subjected to oxidation passivation treatment to obtain the product.
[0014] The Si@C negative electrode material with a three-dimensional porous structure surface is prepared, and its internal pore space can accommodate the volume expansion of the active material, accelerate the interfacial electrochemical reaction, and promote the transfer of electrons / ions. Then, a three-dimensional porous structure is constructed on the surface of the core-shell structure by further vapor deposition or sol-gel method. This step is intended to increase the specific surface area of the material, improve the transmission rate of ions and electrons, and buffer the volume expansion through a large and elastic three-dimensional porous structure, and maintain the integrity of the Si electrode during the cycle.
[0015] Finally, an oxidized passivation layer is prepared on the surface of the material, which can further play a protective role, prevent the negative electrode material from direct contact with the electrolyte, and improve the stability of the material.
[0016] In some embodiments, the pore volume of the porous carbon material is 0.5-1 cm 3 / g, average pore size is 2-3nm, specific surface area is 1500-2000m 2 / g.
[0017] Preferably, the pore volume of the porous carbon material is 0.7-1 cm 3 / g, average pore size of 2-2.5nm, specific surface area of 1700-2000m 2 / g.
[0018] More preferably, the pore volume of the porous carbon material is 0.9 cm 3 / g, average pore size of 2.1nm, specific surface area of 1850m 2 / g.
[0019] In some embodiments, the nano-silicon layer is deposited by vapor deposition. Since the activation energy of the silicon source gas entering the pores is less than the activation energy required for deposition on the surface, the silicon source gas is more easily deposited on the porous carbon pore walls.
[0020] Preferably, the vapor phase silicon source used in the vapor deposition method is monosilane or dimethylsilylamine.
[0021] Preferably, when the nano-silicon layer is vapor deposited, the deposition temperature is 500-600° C. and the deposition time is 5-10 h.
[0022] Further preferably, before the silicon source gas is introduced, the step of raising the temperature to the deposition temperature and maintaining the temperature for 10 minutes to 2 hours is also included.
[0023] In some embodiments, the carbon coating layer is prepared by vapor deposition or sol-gel method.
[0024] Preferably, when the carbon coating layer is prepared by vapor deposition, the preparation environment is heated to 550-650° C. in a hydrogen-argon mixed atmosphere, and then a carbon source gas is introduced for carbon coating.
[0025] More preferably, the carbon coating time is 3-5 hours.
[0026] In a third aspect, the present invention provides a battery, wherein the negative electrode material on the negative electrode plate of the battery is the silicon-carbon negative electrode material.
[0027] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0028] The present invention constructs a three-dimensional porous structure on the silicon carbon surface, increases the specific surface area of the material, improves the transmission rate of ions and electrons, improves the conductivity and cycle stability of the material, and alleviates the volume effect of silicon.
[0029] The preparation method of the present invention performs step-by-step operations on silicon deposition and carbon coating, which can achieve precise control of the silicon deposition and carbon coating processes. By adjusting deposition parameters (such as temperature, pressure, time, etc.), the deposition morphology of silicon and the coating effect of carbon can be optimized, thereby obtaining a composite material with a specific structure and performance. And the step-by-step process helps to form a more uniform and dense carbon coating layer. This can not only improve the conductivity and structural stability of the material, but also reduce the direct contact between silicon and the electrolyte, reduce the occurrence of side reactions, and thus improve the performance and cycle stability of the battery.
[0030] The preparation method is simple, has low raw material cost, strong operability, and is environmentally friendly, so that the lithium-ion battery has good rate performance and stable cycle performance. DETAILED DESCRIPTION
[0031] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0032] The present invention will be further described below in conjunction with the embodiments.
[0033] Example 1
[0034] 1. 80L / min of nitrogen was continuously introduced into the reactor as a protective gas source, and then 6kg of porous carbon (the pore volume of the porous carbon substrate is 0.9cm 3 / g, average pore size of 2.1nm, specific surface area of 1850m 2 / g), and then heated to 550°C at a heating rate of 5°C / min. After keeping warm for 10 minutes, monosilane gas was introduced at a rate of 5L / min. The temperature was kept warm for 8 hours, and then cooled to room temperature.
[0035] 2. The silicon-carbon material prepared above was placed in a tubular furnace, and the temperature was raised to 600°C at 2.5°C / min in a hydrogen-argon (the volume ratio of hydrogen to argon was 5:95) atmosphere, and kept warm for 2 hours. Ethylene gas (2 L / min) was introduced and kept warm for 4 hours.
[0036] 3. Cool down to 300°C, and introduce a mixture of oxygen-containing gas and carrier gas into the deposition furnace. The volume fraction of oxygen in the mixed gas is 3%, and the surface is passivated. This step is to form an oxide layer on the surface of the material to prevent the negative electrode material from directly contacting the electrolyte and improve the stability of the material.
[0037] 4. The prepared silicon-carbon negative electrode material is subjected to post-processing steps such as washing and drying, so as to prepare a carbon-coated silicon-carbon negative electrode material having a three-dimensional porous structure on the surface.
[0038] Example 2
[0039] 1. 90L / min of nitrogen was continuously introduced into the reactor as a protective gas source, and then 6.5kg of porous carbon (the pore volume of the porous carbon substrate is 0.9cm 3 / g, average pore size of 2.1nm, specific surface area of 1850m 2 / g), and then heated to 600°C at a heating rate of 3°C / min. After keeping warm for 10 min, monosilane gas was introduced at a rate of 5 L / min. The temperature was kept warm for 8 h, and then cooled to room temperature.
[0040] 2. The silicon-carbon material prepared above was placed in a tubular furnace, and the temperature was raised to 600°C at 2.5°C / min in a hydrogen-argon (the volume ratio of hydrogen to argon was 5:95) atmosphere, and kept warm for 2 hours. Ethylene gas (2 L / min) was introduced and kept warm for 4 hours.
[0041] 3. Cool down to 250°C, and introduce a mixture of oxygen-containing gas and carrier gas into the deposition furnace. The volume concentration of oxygen in the mixed gas is 3% for surface passivation. This step is to form an oxide layer on the surface of the material to prevent the negative electrode material from directly contacting the electrolyte and improve the stability of the material.
[0042] 4. The prepared silicon-carbon negative electrode material is subjected to post-processing steps such as washing and drying, so as to prepare a carbon-coated silicon-carbon negative electrode material having a three-dimensional porous structure on the surface.
[0043] Example 3
[0044] 1. 90L / min of nitrogen was continuously introduced into the reactor as a protective gas source, and then 6.5kg of porous carbon (the pore volume of the porous carbon substrate is 1.0cm 3 / g, average pore size is 2.0nm, specific surface area is 1800m 2 / g), and then heated to 550°C at a heating rate of 5°C / min. After keeping warm for 15 minutes, monosilane gas was introduced at a rate of 5.5L / min. The temperature was kept warm for 6 hours, and then cooled to room temperature.
[0045] 2. The silicon-carbon material prepared above was placed in a tubular furnace, and the temperature was raised to 650°C at 2.5°C / min in a hydrogen-argon (the volume ratio of hydrogen to argon was 5:95) atmosphere, and kept warm for 2 hours. Ethylene gas (2L / min) was introduced and kept warm for 4 hours.
[0046] 3. Cool down to 200°C, and introduce a mixture of oxygen-containing gas and carrier gas into the deposition furnace. The volume concentration of oxygen in the mixed gas is 3% for surface passivation. This step is to form an oxide layer on the surface of the material to prevent the negative electrode material from directly contacting the electrolyte and improve the stability of the material.
[0047] 4. The prepared silicon-carbon negative electrode material is subjected to post-processing steps such as washing and drying, so as to prepare a carbon-coated silicon-carbon negative electrode material having a three-dimensional porous structure on the surface.
[0048] Comparative Example 1
[0049] 1. 80L / min of nitrogen was continuously introduced into the reactor as a protective gas source, and then 6kg of porous carbon (the pore volume of the porous carbon substrate is 0.9cm 3 / g, pore size is 2.1nm, specific surface area is 1850m 2 / g), and then heated to 550°C at a heating rate of 5°C / min. After keeping warm for 10 min, monosilane gas was introduced at a rate of 5 L / min, and the temperature was kept warm for another 8 h.
[0050] 2. Cool down to 300°C, and introduce a mixture of oxygen-containing gas and carrier gas into the deposition furnace for surface passivation. This step is to form an oxide layer on the surface of the material to prevent the negative electrode material from directly contacting the electrolyte and improve the stability of the material.
[0051] 3. The prepared silicon-carbon negative electrode material is subjected to post-processing steps such as washing and drying.
[0052] Comparative Example 2
[0053] The difference from Example 1 is that 80 L / min of nitrogen is continuously introduced into the reactor as a protective gas source, and then 6 kg of porous carbon (the pore volume of the porous carbon substrate is 0.9 cm 3 / g, average pore size of 2.1nm, specific surface area of 1850m 2 / g), heated to 550°C at a heating rate of 5°C / min, and kept warm for 10 min. At the same time, the atmosphere was replaced with hydrogen-argon (the volume ratio of hydrogen to argon was 5:95), and then a mixed gas of monosilane gas and ethylene was introduced, with a gas volume of 5 L / min for monosilane gas and a flow rate of 2 L / min for ethylene. The temperature was kept warm for 8 h, and then the temperature was lowered to room temperature.
[0054] The rest are the same as in Example 1.
[0055] Performance Test:
[0056] The Si@C negative electrode materials provided in Example 1-3 and Comparative Example 1-2 are used to prepare a battery. The specific steps of preparing the battery include:
[0057] Graphite, silicon negative electrode material, conductive agent and binder were mixed and dissolved in a solvent in a mass ratio of 90:6:1:3, the solid content was controlled at 55%, coated on a copper foil current collector, and vacuum dried to obtain a button battery assembled with a negative electrode plate, electrolyte, SK separator, lithium plate and shell using a conventional production process; wherein the solvent of the electrolyte was ethylene carbonate (EC): dimethyl carbonate (DMC): ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1; the solute was LiPF6, and the concentration of the solute was 1 mol / L; the electrical performance of the battery was tested on a battery test system. The test conditions were: at room temperature, 0.1C constant current charge and discharge, charge and discharge cut-off voltage 0.01V-1.5V, and the test results were shown in Table 1.
[0058] The other parameters remain unchanged, the charging current is changed, and the rate retention rate of the battery is tested. The results are shown in Table 1.
[0059] Table 1 Comparison of electrical properties of examples and comparative examples
[0060]
[0061] As shown in Table 1, by modifying the surface of silicon-carbon materials and constructing a three-dimensional porous structure, an effective buffer space and transmission channel are provided for silicon particles, which improves the structural stability and cycle performance of the material. At the same time, the uniform deposition of nano-silicon particles and the construction of a three-dimensional porous structure also increase the specific surface area and electrochemical activity of the material, thereby improving the energy density of the battery. The preparation method is simple, has low raw material cost, strong operability, and is environmentally friendly, so that lithium-ion batteries have good rate performance and stable cycle performance. And the step-by-step silicon deposition and carbon coating can ensure the uniformity and stability of the material, thereby improving the battery's electrical performance and cycle stability.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A silicon-carbon negative electrode material, characterized in that: The invention comprises a porous carbon substrate, a nano silicon layer deposited on the surface of the porous carbon substrate, a carbon coating layer deposited on the surface of the nano silicon layer and a passivation layer attached to the surface of the carbon coating layer.
2. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The method comprises the following steps: placing the porous carbon material in an inert atmosphere, heating it for pretreatment, and removing impurities and moisture on the surface of the material; Vapor-depositing a nano-silicon layer on the surface of the pretreated porous carbon material; Then, a carbon coating layer is deposited on the surface of the nano-silicon layer; The surface of the carbon coating layer is subjected to oxidation passivation treatment to obtain the product.
3. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: The pore volume of the porous carbon material is 0.5-1 cm 3 / g, average pore size is 2-3nm, specific surface area is 1500-2000m 2 / g.
4. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: The pore volume of the porous carbon material is 0.7-1 cm 3 / g, average pore size of 2-2.5nm, specific surface area of 1700-2000m 2 / g; Preferably, the pore volume of the porous carbon material is 0.9 cm 3 / g, average pore size of 2.1nm, specific surface area of 1850m 2 / g.
5. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: The nano-silicon layer is deposited by vapor deposition method.
6. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: The gas phase silicon source used in the vapor deposition method is monosilane or dimethylsilylamine.
7. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: When the nano-silicon layer is vapor deposited, the deposition temperature is 500-600°C and the deposition time is 5-10h; Preferably, before the silicon source gas is introduced, the step of raising the temperature to the deposition temperature and maintaining the temperature for 10 minutes to 2 hours is also included.
8. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: The carbon coating layer is prepared by vapor deposition or sol-gel method.
9. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: When the carbon coating layer is prepared by vapor deposition, the preparation environment is heated to 550-650° C. in a hydrogen-argon mixed atmosphere, and then a carbon source gas is introduced for carbon coating; Preferably, the carbon coating time is 3-5 hours.
10. A battery, characterized in that: The negative electrode material on the negative electrode plate is the silicon-carbon negative electrode material according to claim 1, or the silicon-carbon negative electrode material prepared by any preparation method according to claims 2-9.
Citation Information
Patent Citations
Negative electrode material as well as negative electrode plate and battery comprising negative electrode material
CN114864909A
Silicon-carbon composite material, preparation method and application thereof, and lithium ion secondary battery
CN116742002A
Negative electrode material and preparation method and application thereof
CN118993035A
Negative electrode and method for producing negative electrode
US20240363840A1
Cited By
Preparation method of vapor deposition silicon carbon material based on supercritical carrier gas
CN120767282A
Silicon-carbon negative electrode material, preparation method and application thereof, and battery negative electrode
CN120933333A